Are presynaptic GABA-Cρ2 receptors involved in anti-nociception?. (8th October 2015) - Tadavarty, R.; Hwang, J.; Rajput, P.S.; Soja, P.J.; Kumar, U.; Sastry, B.R.
Highlights: GABA-C receptors are anti-nociceptive. The ρ2 type are expressed presynaptically in lumbar dorsal horn of the spinal cord. Analgesic effects could be via control of nociceptive input in substantia gelatinosa. Abstract: We investigated the anti-nociceptive effects of GABA-C receptors in the central nervous system. Intracisternal injection of CACA, a GABA-C receptor agonist or isoguvacine, a GABA-A receptor agonist, significantly increased the tail-withdrawal latency. TPMPA, a GABA-C receptor antagonist blocked the effects of CACA but not isoguvacine indicating that GABA-C receptors are involved in regulating pain. Further, double-labelled immunofluorescence studies revealed that GABA-Cρ2 receptors are expressed presynaptically in the spinal dorsal horn, especially, substantia gelatinosa, a region that has been previously implicated in analgesia by regulating nociceptive inflow. These data provide a provenance for future work looking at presynaptic spinal GABA-C receptors in the control of nociception.